Principals' Leadership Style and School Perfonnance: Case of Selangor Secondary Schools - Yaakub, Noran Fauziah; Ayob, Ahmad Mahdzan (Universiti Putra Malaysia Press, 1993)
The purpose of this study was to explain overall school performance in terms of principals' leadership style and some school background factors. Data were collected from 69 schools from the state of Selangor. Four independent variables were used in the regression model to explain overall school performance in the Malaysian Certificate Examination (MCE). The results showed all the four independent variables in the regression model, i.e. principal's leadership style, age of school, small town and rural schools correlate significantly with overall school performance.